Prospects for use of strength exercises under unstable work posture as a method of increasing strength abilities n highly qualified biathlonists - Kryuchkov, A. S.; Fedotova, E. V.; Sidelev, P. A.; Myakinchenko, E. B. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to reveal, on the basis of a theoretical analysis, training effects when using strength exercises in an unstable working posture and to evaluate the prospects for their use as a method of increasing the specific strength of highly qualified biathletes.